Celep, F., Karaer, F., Duman, H. (2021) Resurrection of Lamium ponticum (Lamiaceae) with a new subspecies, Lamium ponticum subsp. anatolicum, from Turkey. Phytotaxa 511 (1): 071‒076. - Celep, Ferhat; Karaer, Fergan; Duman, Hayri (Phytotaxa, 2021)
N/A